A probabilistic modeling framework for data-driven forecasting of rainfall-induced debris flows - Siling Zhang; Xiaojun Guo; Yong Li; Jianyi Cheng (Journal of Hydrology, 2026)

Integrated Multi-omics Reveals CDKN1A Suppression and Metabolic Regulation as Key Mechanisms of Huangqi Guizhi Wuwu Decoction Against Doxorubicin-Induced Cardiotoxicity - Qian Hou; Xinyue Yu; Ke Wu; Siling Chen; Xin Mao; Xinying Qian; Changjin Li; Lidan Sheng; Ruiping Wang; Yin Huang (Cardiovascular Toxicology, 2026)

A unified fractional-order model for soil infiltration - Xinyi Guo; Xiaojun Guo; Yong Li; Siling Zhang; Jianyi Cheng (Journal of Hydrology, 2026)

Unified functions between shear strength parameters and GSD parameters in wide-graded soils - Jianyi Cheng; Xiaojun Guo; Yong Li; Siling Zhang (Engineering Geology, 2026)

Humanoid animal behavior labeler: An interactive annotation agent to accelerate ethological applications in precision management of animals using large vision-language models - Mengting Zhou; Siling Zhou; Benhai Xiong; Zimu Li; Isabella C.F.S. Condotta; Ryan N. Dilger; Jiangong Li; Xiangfang Tang (Computers and Electronics in Agriculture, 2026)

Revealing the significance of melatonin in postharvest quality of tomato fruit, especially in sugar metabolism and transport - Yunzhi Liu; Yiping Feng; Siling Chen; Yuna Pan; Junrong Xu; Wenjin Yu; Changxia Li (Postharvest Biology and Technology, 2026)

Nanozymes in the field of arthritis applications: classification, mechanisms, and combination therapy - Junhong Zhou; Zhu Liu; Qiuling Deng; Ruowen Li; Yi'an Li; Jinya Xiong; Yuanqi Yang; Siling Wang; Yan Xiao; Qinfu Zhao (Chemical Engineering Journal, 2025)

Rainfall thresholds of debris flows built with assistance of artificial intelligence in a small catchment - Siling Zhang; Xiaojun Guo; Jianyi Cheng; Yong Li (Journal of Hydrology, 2025)

A copper-doped mesoporous nanoplatform with dual enzyme-mimic activities for amplified cuproptosis and immune response - Qingqing Xu; Shuaipeng Feng; Yue Cao; Yang Li; Zhu Liu; Qiuling Deng; Jiaru Lan; Donghua Di; Yuling Mao; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Ginger exosome-covered mesoporous polydopamine nanoplatform ameliorates liver fibrosis via antioxidation and macrophage phenotypic transformation - Junhong Zhou; Hongwei Xu; Zhu Liu; Yuling Mao; Yian Li; Liwan He; Shuaipeng Feng; Donghua Di; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Single-cell resolution reveals the cell types and transcriptomic landscape of the ovary in mandarin fish (Siniperca chuatsi) - Siling Zhang; Jie Ren; Shanwen Jiang; Xiaomin Miao; Yixi Tao; Ronghua Wu; Yun Li; Hao Xu (Aquaculture, 2025)

Research on ship dynamic feature extraction and prediction method based on visual data - Siling Lin; Yong Li; Yu Hu; Jia Shi; Shaohua Wang; Peng Wang; Qiang Mei; Xiao Li; Haowen Wei (Ocean Engineering, 2025)

Multifunctional dynamic chitosan-guar gum nanocomposite hydrogels in infection and diabetic wound healing - Luning He; Shuyi Xing; Weikang Zhang; Ying Wang; Yian Li; Jinghao Chen; Jinghai Zhang; Siling Wang; Qinfu Zhao (Carbohydrate Polymers, 2025)

Construction of a lightweight, bispecific human antibody based on the bovine nano knob domain - Siling Wang; Yizhen Wang; Xiuting Chen; Wenling Jiang; Zheng Chen; Huixian Shang; Zhiyong Li; Zizheng Zheng; Ningshao Xia (Science China Life Sciences, 2025)

Accelerated Data Engine: A faster dataset construction workflow for computer vision applications in commercial livestock farms - Yiqi Wu; Siling Zhou; Zhonghong Wu; Zhaohui Chen; Xiaodan Hu; Jiangong Li (Computers and Electronics in Agriculture, 2024)

Lipidomics and transcriptomics analysis revealed the role of the spleen of Nile tilapia (Oreochromis niloticus) in lipid metabolism - Yixi Tao; Yanling Chen; Jie Ren; Shanwen Jiang; Siling Zhang; Hao Xu; Yun Li (Aquaculture, 2024)

A new intracellularly regulated release pattern controlled by coordinated carrier cracking and drug release - Xinyue Zhang; Ye He; Zhiqi Wang; Ying Zhang; Wen Guo; Shuai Li; Xinyu Wang; Yuling Mao; Siling Wang (Chemical Engineering Journal, 2024)

Legacy and alternative perfluoroalkyl acids in the Yellow River on the Qinghai-Tibet Plateau: Levels, spatiotemporal characteristics, and multimedia transport processes - Wu Wen; Lijuan Gao; Hao Cheng; Lu Xiao; Shangwei Zhang; Siling Li; Xiaoman Jiang; Xinghui Xia (Water Research, 2024)

Toxicity mechanism of acrolein on energy metabolism disorder and apoptosis in human ovarian granulosa cells - Xueping Liu; Rongxia Li; Zi Xiu; Siling Tang; Yancang Duan (Toxicology, 2024)

Metabolomics analysis of splenectomy of Nile tilapia (Oreochromis niloticus) reveals the spleen involved in regulating liver lipids and amino acids metabolism - Yixi Tao; Chunying Du; Shanwen Jiang; Siling Zhang; Jingyun Feng; Xiaomin Miao; Hao Xu; Yun Li (Frontiers in Marine Science, 2024)
The liver is essential for nutritional balance in fish, and liver damage in farmed fish often arises from factors like overfeeding, causing various health issues. Clinical observations indicate that liver diseases frequently involve spleen dysfunction, and there is evidence to suggest that the spleen has a significant impact on liver function. However, there has been no discussion on the role of the spleen in maintaining liver health in fish. To understand the role of fish spleen in liver metabolism, this study selected Nile tilapia ( Oreochromis niloticus ) as the experimental material and first established a tilapia splenectomy model. Various biochemical parameters of the liver and serum were measured, and the liver metabolism characteristics of the splenectomy group (SP group) and the sham operation group (SO group) were analyzed using metabolomics. After splenectomy, biochemical parameters of the liver and serum showed abnormalities, including significant increases in total cholesterol (T-CHO) and serum total bile acid (TBA) levels, alongside a significant decrease in liver TBA levels, suggesting impaired metabolic function and cholesterol deposition in the liver. Metabolomics analysis showed that metabolites such as lipids, lipid-like molecules, and organic acids and derivatives were differentially regulated between the SO and SP group. KEGG analysis showed that differential metabolites were enriched in lipid metabolism and amino acid metabolism. The metabolic pathway analysis of differential metabolites showed that after splenectomy, the low-activity urea cycle in the liver may accelerate lipid synthesis, while low concentrations of aromatic amino acids and taurine may inhibit lipid catabolism. These results indicate that after splenectomy, the liver metabolic capacity is impaired, which causes abnormal lipid metabolism by interfering with amino acid metabolism, making splenectomy tilapia liver at risk of liver disease, including cholesterol deposition, hepatic steatosis and nonalcoholic fatty liver disease (NAFLD). Our results show that the spleen is involved in regulating liver lipid and amino acid metabolism, and the spleen may interfere with lipid metabolism by regulating liver amino acid metabolism. Our data can provide support for further research on liver and spleen functions and the immune-nutrient metabolism mechanisms in fish, as well as new ideas for healthy fish farming.

Current advances in porous organic nanoplatforms for tumor theranostics - Wanhao Qi; Bin Liu; Yian Li; Zhu Liu; Shiqiao Rui; Shuaipeng Feng; Junya Lu; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2024)

Feasibility of biodegradable material polylactic acid as a substitute for polypropylene for disposable medical masks production verified by life cycle assessment - Liting Hao; Siling Ren; Jiayong Li; Xiangyang Wang; Lin Li; Xiaodi Hao (Journal of Cleaner Production, 2024)

Cytological observations in abortion formation and morphological character of pollen in seedless chestnut rose (Rosa sterilis) - Qian Du; Kui Zhou; Siling Zhong; Changying Li; Jinbu Fan; Qian Wang; Yi Hong; Xiaopeng Wen (Flora, 2023)

A novel oral biomimetic delivery system enhancing both the mucosal and systemic immunity of influenza virus vaccine - Hongyan Lu; Yikun Gao; Jianmin Chen; Jing Chai; Ansheng Li; Tongtong Sun; Yuling Mao; Ye He; Qinfu Zhao; Jinghai Zhang; Siling Wang (Chemical Engineering Journal, 2023)

A female in vivo haploid-induction system via mutagenesis of egg cell-specific peptidases - Xuecheng Zhang; Ce Shi; Siling Li; Bo Zhang; Pan Luo; Xiongbo Peng; Peng Zhao; Thomas Dresselhaus; Meng-Xiang Sun (Molecular Plant, 2023)

A Novel Three-Dimensional Large-Pore Mesoporous Carbon Matrix as a Potential Nanovehicle for the Fast Release of the Poorly Water-soluble Drug, Celecoxib - Yanzhuo Zhang; Hong Wang; Chuanjun Li; Baoxiang Sun; Yu Wang; Siling Wang; Cunqiang Gao (Pharmaceutical Research, 2014)